Mechanical Properties of Na2CO3-Activated High-Volume GGBFS Cement Paste - Taewan Kim; Yubin Jun (Advances in Civil Engineering)
The use of Na2CO3 to improve the mechanical properties of high-volume slag cement (HVSC) is experimentally investigated in this study. Ordinary Portland cement (OPC) was replaced with 50, 60, 70, 80, and 90% ground-granulated blast-furnace slag (GGBFS) by weight. Na2CO3 was added at 0, 1, 2, 3, 4, and 5 wt.% of HVSC (OPC + GGBFS). The compressive strength, water absorption, ultrasonic pulse velocity, dry shrinkage, and X-ray diffraction spectra of the Na2CO3-activated HVSC pastes were analyzed. The results indicate that Na2CO3 was effective for improving the strength of HVSC samples at both early and later ages. There was a trend of increasing HVSC sample strength with increasing Na2CO3 content. The 5% Na2CO3-activated HVSC (50% OPC + 50% GGBFS) paste had the best combination of early to later-age strength development and exhibited the highest UPV and the lowest water absorption among the Na2CO3-activated HVSC samples at later age.